2018
DOI: 10.1002/oby.22322
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐Induced Paternal Obesity Impairs Cognitive Function in Offspring by Mediating Epigenetic Modifications in Spermatozoa

Abstract: Objective This study aimed to determine the effects of diet‐induced paternal obesity on cognitive function in mice offspring. Methods Male mice (F0) were randomized to receive either a control diet (10 kcal% fat) or a high‐fat diet (HFD; 60 kcal% fat) for 10 weeks before being mated with normal females to generate F1 offspring. Male F1 offspring were mated with normal females to generate F2 offspring. Behavioral tests were used to assess cognitive functions in F1 and F2 offspring. Reduced representation bisulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Consistent with the latter possibility, animal studies have shown that pups born to obese dams exhibit heightened and anxiety and depression-like behaviors [101]. Paternal obesity may also adversely impact cognitive and behavioral outcomes in offspring by epigenetic mechanisms [102,103]. Collectively, the emerging data suggest that overconsumption of high-energy foods by conceiving mothers and fathers increase the risk of poor or suboptimal cognitive outcomes of their offspring.…”
Section: Transgenerational Epigenetic Impact Of Excessive Food Intakementioning
confidence: 92%
“…Consistent with the latter possibility, animal studies have shown that pups born to obese dams exhibit heightened and anxiety and depression-like behaviors [101]. Paternal obesity may also adversely impact cognitive and behavioral outcomes in offspring by epigenetic mechanisms [102,103]. Collectively, the emerging data suggest that overconsumption of high-energy foods by conceiving mothers and fathers increase the risk of poor or suboptimal cognitive outcomes of their offspring.…”
Section: Transgenerational Epigenetic Impact Of Excessive Food Intakementioning
confidence: 92%
“…Epigenetic inheritance refers to heritable changes in phenotypes that are independent of changes to the DNA sequence. Environmental insults, such as change in diet (Carone et al 2010;Dunn and Bale 2011;Watkins et al 2018;Zhou et al 2018), exposure to drugs of abuse (Le et al 2017;Vassoler et al 2013;Yohn et al 2015), and stress (Bale 2015;Morgan and Bale 2011;Rodgers et al 2013b;Rodgers et al 2015) have been shown to cause epigenetic changes in male germ cells. Exposure to drugs of abuse changes several components of the epigenetic landscape, including acetylation of histones and DNA methylation in sperm of both rodents (Le et al 2017;Vassoler et al 2013) and humans (Chorbov et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…28 Paternal obesity may also relate to child behavioral problems or psychiatric symptoms as evidence from animal studies has revealed mechanisms for non-mendelian epigenetic inheritance. 29 Previous studies investigated the associations of paternal obesity with child behavioral problems and psychiatric symptoms; two did not find an association between paternal obesity and child behavioral problems 12,18 , one observed a positive, but imprecise, association with ADHD symptoms, 26 and, in the largest study, a positive association between paternal obesity and offspring behavioral problems was observed. 15 An association with maternal but not paternal obesity would support the hypothesis that alterations in the intrauterine environment, rather than preconception or postnatal factors shared between parents (e.g., diet)are implicated in the development of offspring behavioral problems and psychiatric symptoms.…”
mentioning
confidence: 98%